Plantar pressure distribution in elderly subjec Ts after proprioceptive exercises - Fábio Marcon Alfieri (Universidade Federal de Santa Catarina, 2008)
Changes related to aging limit cutaneous plantar perception, interfering in postural control. The aim of this study was to verify the effects of a regular program of proprioceptive intervention on plantar pressure distribution in older adults. Plantar pressure distribution was evaluated in 29 volunteers (63.06 ±2.84 years) standing on both feet with eyes open (EO) and eyes closed (EC). After baropodometric evaluation, the subjects attended 3 weekly proprioceptive intervention sessions of 1 hour's duration for 3 months. Results: Prior to the intervention, participants exhibited mean EO values of 0.29 ±0.044 Kg/cm² for the right foot and 0.31 ±0.04 Kg/cm² for the left foot (p=0.0078) and post-intervention these were 0.28±0.04 Kg/cm² and 0.30±0.04 Kg/cm², respectively. Pre-intervention EC values were 0.30 ±0.044 Kg/cm² for the right and 0.31 ±0.05 Kg/cm² for the left foot and post-intervention these figures were 0.28 ±0.04 Kg/cm² and 0.29 ±0.049 Kg/cm², respectively. The results of MANOVA indicated significant differences in contact pressure between pre-intervention and post-intervention measurements. Conclusions: The intervention used here reduced the participants' plantar pressure, but was unable to improve the distribution of plantar pressure between the right and left feet. Resumo Alterações decorrentes do envelhecimento limitam a percepção cutâneo-plantar, interferindo no controle postural. O objetivo deste trabalho foi de verificar os efeitos de um programa regular de intervenção proprioceptiva sobre a distribuição da pressão plantar em idosos. Avaliou-se a distribuição da pressão plantar em 29 indivíduos (63,06 ±2,84 anos) em apoio bipodal com olhos abertos (BA) e fechados (BF). Após avaliação baropodométrica, iniciou-se intervenção proprioceptiva (3 sessões semanais de 1 hora) durante 3 meses. No apoio BA, os indivíduos apresentaram valor médio de 0,29±0,044 Kg/cm² no pé direito e de 0,31± 0,04 Kg/cm² no pé esquerdo pré-intervenção, passando para 0,28±0,04 Kg/cm² e 0,30± 0,04 Kg/cm² após a intervenção, respectivamente. No apoio BF, os voluntários apresentaram 0,30±0,044 Kg/cm²no pé direito e 0,31±0,05 Kg/cm² no pé esquerdo antes da intervenção, e 0,28±0,04 Kg/cm² e 0,29±0,049 Kg/cm² após a intervenção respectivamente. A Manova revelou diferença significativa para a pressão de contato entre as condições pré e pós-intervenção. A intervenção aplicada pôde diminuir a pressão plantar dos indivíduos, porém não foi capaz de melhorar a distribuição da pressão plantar entre os pés direito e esquerdo.